The Role of Texture and Materiality in Enhancing Realism in Still Life Painting - Tolibova Umida Davlat qizi (SCIENCE AND CULTURE: INNOVATIONS OF THE 21ST CENTURY, 2025)
ANNOTATION: This article explores the role of texture and materiality in enhancing realism and expressiveness in still life painting. It discusses how different surfaces, materials, and tactile qualities influence visual perception and the overall aesthetic experience of a composition. The study also highlights pedagogical approaches for teaching students to observe, interpret, and represent texture effectively, drawing on Shovdirov S.A.’s research in visual arts education.